Motivasi dan Kemampuan Petani dalam Pengelolaan Usahatani Nilam di Desa Parura Kecamatan Tiworo Selatan Kabupaten Muna Barat - Indah Maryani Yustika; Yani Taufik; Salahuddin Salahuddin (Jurnal Ilmiah Penyuluhan dan Pengembangan Masyarakat, 2022)
The goal of this research is to determine the amount of farmer motivation and ability, as well as the link between the two in patchouli crop management. The census technique was utilized in this study. The analysis of the data used is processed by a class interval expression and is a quantitative description method for finding the relationship with Spearman's rank correlation expression. The findings reveal that intrinsic motivation, or willingness from within, which comprises of wants and expectations, influences farmers' motivation to plant patchouli, whereas interest is insufficient to encourage farmers to grow patchouli. Meanwhile, extrinsic motivation consisting of family and environmental support is also not strong enough to motivate farmers to plant patchouli.The ability of farmers to plant patchouli in terms of knowledge and skills is high, although farmers are still not perfect in implementing every aspect of activities in planting patchouli. The results of the Rank Sperman correlation test show that motivation is significantly related to ability. The better the farmer's motivation, the greater his ability, and vice versa, the higher the farmer's ability and motivation.